Introduction: The Poetics of the Eruv - Olin, Margaret (Images, 2011)
Abstract The eruv is a talmudic provision that permits orthodox Jews to carry small objects outside of their homes on the Sabbath, a practice that would otherwise be forbidden on that day. Often intended to be visible, it is marked in a variety of ways with a range of materials, and frequently serves as a metaphor for relations within a community, as suggested in the articles and works of art included in the symposium and portfolio to which this essay serves as an introduction.